Analisis implementasi budaya sekolah berbasis islami dalam membangun karakter disiplin siswa di sekolah dasar islam terpadu - Herlina Dwi Haryati; Jenny Indrastoeti Siti Poerwanti; Tri Budiharto (Didaktika Dwija Indria, 2023)
The aims of this study are: (1) to analyze the implementation of Islamic-based school culture in building the disciplinary character of students at SDIT Al-Hadi; (2) analyzing the supporting factors and inhibiting factors for the implementation of Islamic-based school culture in building the disciplinary character of students at SDIT Al-Hadi; (3) analyzing the efforts made to overcome the inhibiting factors of implementing Islamic-based school culture in building the disciplinary character of students at SDIT Al-Hadi. This study uses a descriptive qualitative research approach. The subject in this study were the principal, teachers and students of SDIT Al-Hadi. Data collection techniques using observation, interviews and documentation. Data validity testing technique uses source triangulation and technical triangulation. Data analysis techniques use interactive model data analysis. The results of this study indicate that: (1) The implementation of Islamic-based school culture in building disciplinary character at SDIT Al-Hadi has been carried out very well at a scale of 90%; (2) Factors supporting, namely: the involvement of school members and supporting infrastructure. The inhibiting factors are: students easily forget and lack of student awareness; (3) Efforts made to overcome the inhibiting factors are: raising student awareness and establishing cooperation with parents.